EVA / LDHs modifier as well as preparation method and application thereof

By combining sheet-like calcined hydrotalcite with ethylene-vinyl acetate latex powder, the EVA/LDHs modifier is solved, and the problem of high-performance concrete being susceptible to salt freezing in severe cold areas is significantly improved. The mechanical properties of concrete are significantly improved and Durability.

CN119461936APending Publication Date: 2025-02-18JILIN TRAFFIC SCI ACAD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411683680.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing high-performance concrete is susceptible to salt freezing in severe cold areas, resulting in reduced mechanical properties and shortened service life.

Method used

The EVA/LDHs modifier is used to combine sheet-like calcined hydrotalcite (CLDH) with ethylene-vinyl acetate latex powder (EVA). The EVA/LDHs modifier prepared can significantly enhance the concrete. Mechanical properties and salt freezing resistance.

Benefits of technology

EVA/LDHs modifiers significantly improve the compressive and tensile mechanical properties of concrete, and reduce salt erosion through the adsorption of CLDH, improving the durability and service life of concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461936A_ABST
    Figure CN119461936A_ABST
Patent Text Reader

Abstract

The invention provides an EVA / LDHs modifier as well as a preparation method and application thereof, and belongs to the technical field of concrete modifiers, the preparation method comprises the following steps: calcining lamellar hydrotalcite, cooling to room temperature, sieving to obtain lamellar calcined hydrotalcite, adding ethylene-vinyl acetate latex powder and lamellar calcined hydrotalcite into deionized water, heating and stirring, then standing, filtering, and drying to obtain the EVA / LDHs modifier. Cooling to room temperature to obtain an EVA / LDHs solution, centrifuging and drying the EVA / LDHs solution, and sequentially grinding and sieving to obtain an EVA / LDHs modifier; the preparation of the EVA / LDHs modifier is realized by accurately controlling key parameters in the preparation process, and the EVA / LDHs modifier disclosed by the invention can be used for improving the mechanical property, salt freezing resistance and durability of HPC (High Performance Concrete), and provides a new material for cement concrete structures with high durability requirements in seasonal freezing regions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete modifiers, and in particular to an EVA / LDHs modifier and a preparation method and application thereof. Background Art

[0002] High Performance Concrete (HPC) is developed on the basis of high-strength concrete. HPC not only has the strength advantage of high-strength concrete, but also has good durability. It can ensure that the concrete structure is not destroyed under the long-term influence of adverse external environment to meet the needs of normal use. The concept of sustainable development of HPC is in line with the current status and development needs of the construction industry. The design concept of HPC is to adopt the closest packing theory, calculate the optimal combination ratio of materials according to the particle size distribution law of different particles of each component in cement-based composite materials, and finally prepare a concrete product with dense structure and less pore structure.

[0003] HPC can block the erosion of salt solutions through its own dense concrete structure, but cement hydration is an exothermic reaction, and the early strength of HPC is formed quickly, generating a large amount of hydration heat. Concrete is a poor conductor of heat, and the heat will accumulate inside the concrete and be difficult to release, generating temperature stress, thereby generating a large number of microcracks at weak interfaces. The repeated action of external loads causes the microcracks to continue to expand, ultimately causing corrosion and damage to the concrete by the salt solution. This phenomenon is particularly evident in extremely cold areas with heavy snowfall in winter, long snowfall duration and low ambient temperature.

[0004] Therefore, how to improve the mechanical properties and salt-freezing resistance of concrete and ensure that the concrete material still has good performance under the influence of long-term external environmental factors is one of the technical problems that need to be solved urgently. Summary of the invention

[0005] The purpose of the present invention is to provide an EVA / LDHs modifier and a preparation method and application thereof, so as to overcome the problems existing in the prior art. The present invention realizes the preparation of the EVA / LDHs modifier by accurately controlling key parameters in the preparation process. The EVA / LDHs modifier of the present invention can be used to improve the mechanical properties, salt-freezing resistance and durability of HPC, and provides a new material for cement concrete structures with high durability requirements in seasonally frozen areas.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows: A method for preparing an EVA / LDHs modifier comprises the following steps: (1) calcining lamellar hydrotalcites (LDHs), cooling them to room temperature, and sieving them to obtain lamellar calcined hydrotalcites (CLDHs); (2) adding ethylene-vinyl acetate latex powder (EVA) and the lamellar calcined hydrotalcite (CLDH) obtained in (1) into deionized water, heating and stirring, and then standing and cooling to room temperature to obtain an EVA / LDHs solution; (3) The EVA / LDHs solution obtained in (2) is centrifuged, dried, ground, and sieved to obtain an EVA / LDHs modifier.

[0007] Furthermore, the calcination temperature in (1) is 500-600°C, the calcination time is 4-6 h, and the calcination heating rate is 7-9°C / min; Furthermore, the mesh size of the sieve in (1) is 100 mesh; Furthermore, the mass ratio of ethylene-vinyl acetate latex powder, lamellar calcined hydrotalcite and deionized water in (2) is 1:(0.5-1.5):50; Furthermore, the heating temperature in (2) is 90-95°C, the heating time is 0.5-1 h, and the stirring speed is 650-700 r / min; Furthermore, the centrifugal speed in (3) is (4000±50) r / min, and the centrifugal time is 30-40 min; Furthermore, the drying temperature in (3) is 95-105°C, and the drying time is 3-5 h; Furthermore, the sieve hole size of the sieving in (3) is 60 mesh.

[0008] An EVA / LDHs modifier is obtained based on the preparation method of the above-mentioned EVA / LDHs modifier.

[0009] An application of the above-mentioned EVA / LDHs modifier as an admixture for preparing high-performance concrete, wherein the EVA / LDHs modifier accounts for 2% to 8% of the mass of the concrete and is used for preparing cement concrete structures with high durability requirements in seasonally frozen areas.

[0010] The above technical solution has the following advantages or beneficial effects: The invention provides a preparation method of an EVA / LDHs modifier. The prepared EVA / LDHs modifier is capable of significantly enhancing the mechanical properties of concrete by combining lamellar calcined hydrotalcite (CLDH) with ethylene-vinyl acetate latex powder (EVA). The lamellar structure of CLDH can form an effective physical reinforcement network in concrete, while EVA provides good adhesion and elasticity. The synergistic effect of the two significantly improves the mechanical properties of concrete such as compression and tension. In a cold and salty environment, concrete is easily corroded by salt freezing, resulting in performance degradation. The CLDH in the EVA / LDHs modifier can effectively adsorb and fix salt ions in a solution, reducing the corrosive effect of salt on concrete. Meanwhile, the elastic properties of EVA can buffer the stress generated by salt freezing cycles, thereby improving the durability of concrete and extending the service life of concrete.

[0011] Furthermore, by controlling the calcination temperature, time and heating rate, it can be ensured that the interlayer water molecules and anions of the lamellar hydrotalcites (LDHs) are effectively removed, which helps to form a more compact and stable composite material in the subsequent EVA bonding process.

[0012] Furthermore, CLDH particles with uniform particle size screened out by screening can better combine with the EVA matrix, which helps to form a tighter interface; at the same time, the modifier with uniform particle size is more stable during storage and use, and is not prone to stratification or agglomeration, which helps to maintain the stability of the performance of the modifier and extend its service life.

[0013] Furthermore, appropriate reaction temperature and time can ensure that the interaction between EVA latex powder and LDHs reaches the optimal state, thereby improving the physical properties and chemical stability of the product.

[0014] Furthermore, by centrifugal separation, excess water, unreacted raw materials and other impurities in the mixture can be removed, thereby improving the purity of the EVA / LDHs modifier.

[0015] Furthermore, by drying, it can be ensured that the residual moisture in the EVA / LDHs modifier is effectively removed. By controlling the temperature and time, it is possible to ensure the rapid evaporation of the moisture and avoid the thermal decomposition or performance degradation of the modifier caused by excessively high temperature.

[0016] Furthermore, by screening again, the particle size of the EVA / LDHs modifier can be ensured to be within a certain range, avoiding unstable performance caused by too large or too small particle size, and also helping to form a tighter structure in the composite material, thereby improving its physical properties such as strength and hardness.

[0017] The present invention also provides an EVA / LDHs modifier, which can be prepared with excellent performance by controlling specific parameters such as heating temperature, time, stirring speed, centrifugal conditions, drying conditions and sieve hole size, and has high strength, high hardness, good toughness, and excellent wear resistance and corrosion resistance.

[0018] The present invention also provides an application of the above-mentioned EVA / LDHs modifier as an admixture for preparing high-performance concrete. The EVA / LDHs modifier has significant advantages in improving the mechanical properties, salt and frost resistance and durability of concrete, and provides a new material for cement concrete structures with high durability requirements in seasonally frozen areas. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The figure is a schematic flow chart of a method for preparing an EVA / LDHs modifier of the present invention; Figure 2 This is a schematic diagram of the state of the mixed solution after CLDH of the present invention is added to EVA; Figure 3 Schematic diagram of the absorbance of the upper suspension of the EVA / LDHs solution at different reaction temperatures of the present invention; Figure 4 Schematic diagram of absorbance of the upper suspension of the EVA / LDHs solution at different reaction times of the present invention; Figure 5 Schematic diagram of the absorbance of the upper suspension of the EVA / LDHs solution prepared by adding different masses of CLDH in the present invention; Figure 6 The SEM images of the CLDH of the present invention, (a) is a 10 um SEM image of the CLDH, and (b) is a 1 um SEM image of the CLDH; Figure 7 The SEM images of the EVA latex powder of the present invention, (a) is a 50 um SEM image of the EVA latex powder, and (b) is a 1 um SEM image of the EVA latex powder; Figure 8 The SEM images of the EVA / LDHs composite material of the present invention, (a) is a 50 um SEM image of the EVA / LDHs composite material, and (b) is a 1 um SEM image of the EVA / LDHs composite material; Fig. 9 The XRD patterns of different hydrotalcites at 10° to 70° of the present invention; Fig.10 The XRD patterns of the hydrotalcites with different angles of 2° to 10° in the present invention are shown in FIG. Fig.11 It is the infrared spectra of EVA, CLDH and EVA / LDHs of the present invention; Fig.12 It is a schematic diagram of the adsorption capacity of chloride ions in the solution by the EVA / LDHs modifier with different dosages of the present invention; Fig.13 Schematic diagram showing the effect of the dosage of the EVA / LDHs modifier of the present invention on the fluidity of HPC; Fig.14 Schematic diagram of the effect of the dosage of the EVA / LDHs modifier of the present invention on the HPC fold-to-compression ratio; Fig.15 Schematic diagram of the effect of different EVA / LDHs modifier dosages on the chloride ion permeability resistance of HPC according to the present invention, (a) is a schematic diagram of the effect of single EVA and EVA / LDHs on the chloride ion permeability resistance of HPC, (b) is a schematic diagram of the effect of single CLDH and multi-doped 4% EVA + CLDH on the chloride ion permeability resistance of HPC; Fig.16 Schematic diagram of the effect of different EVA dosages on the frost resistance of HPC of the present invention, (a) is a schematic diagram of the compressive strength of HPC with EVA before and after freeze-thaw cycles, (b) is a schematic diagram of the strength loss rate of HPC with EVA after freeze-thaw cycles; Fig.17 Schematic diagram of the effect of different CLDH dosages on the frost resistance of HPC of the present invention, (a) is a schematic diagram of the compressive strength of HPC doped with CLDH before and after freeze-thaw cycles, (b) is a schematic diagram of the strength loss rate of HPC doped with CLDH after freeze-thaw cycles; Fig.18 Schematic diagram of the effect of the 4% EVA+CLDH co-doping on the frost resistance of HPC of the present invention, (a) is a schematic diagram of the compressive strength of HPC co-doped with 4% EVA+CLDH before and after freeze-thaw cycles, (b) is a schematic diagram of the strength loss rate of HPC co-doped with 4% EVA+CLDH after freeze-thaw cycles; Fig.19 Schematic diagram of the effect of adding different amounts of EVA / LDHs on the frost resistance of HPC according to the present invention, (a) is a schematic diagram of the compressive strength of HPC added with EVA / LDHs before and after freeze-thaw cycles, (b) is a schematic diagram of the strength loss rate of HPC added with EVA / LDHs after freeze-thaw cycles; Fig. 20 Schematic diagram of the mass loss rate of HPC doped with EVA / LDHs modifier alone or in combination under the salt freezing cycle of the present invention, (a) is a schematic diagram of the mass loss rate of HPC doped with EVA modifier alone, (b) is a schematic diagram of the mass loss rate of HPC doped with CLDH modifier alone, (c) is a schematic diagram of the mass loss rate of HPC doped with 4% EVA+CLDH modifier, and (d) is a schematic diagram of the mass loss rate of HPC doped with EVA / LDHs modifier of the present invention; Fig.21Schematic diagram of the effect of different EVA dosages on the anti-salt freezing performance of HPC of the present invention, (a) is a schematic diagram of the compressive strength of HPC with EVA before and after salt freezing cycle, (b) is a schematic diagram of the strength loss rate of HPC with EVA after salt freezing cycle; Fig. 22 Schematic diagram of the effect of different CLDH dosages on the anti-salt freezing performance of HPC according to the present invention, (a) is a schematic diagram of the compressive strength of HPC doped with CLDH before and after salt freezing cycle, (b) is a schematic diagram of the strength loss rate of HPC doped with CLDH after salt freezing cycle; Fig.23 Schematic diagram of the effect of the co-addition of 4% EVA+CLDH on the anti-salt freezing performance of HPC of the present invention, (a) is a schematic diagram of the compressive strength of HPC co-addition of 4% EVA+CLDH before and after salt freezing cycle, (b) is a schematic diagram of the strength loss rate of HPC co-addition of 4% EVA+CLDH after salt freezing cycle; Fig.24 Schematic diagram of the effect of different EVA / LDHs dosages on the anti-salt freezing performance of HPC of the present invention, (a) is a schematic diagram of the compressive strength of HPC doped with EVA / LDHs before and after salt freezing cycle, (b) is a schematic diagram of the strength loss rate of HPC doped with EVA / LDHs after salt freezing cycle; Fig.25 The flowchart of the rapid repair construction technology of the expansion joint of the present invention is as follows; Fig.26 A 24-hour open traffic map is completed for the expansion joint repair of the present invention. DETAILED DESCRIPTION

[0020] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it. In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention. It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0021] The raw materials used in the specific implementation of the present invention are as follows: The EVA latex powder is ethylene-vinyl acetate redispersible latex powder produced by Wacker; the LDHs is calcium-aluminum hydrotalcite provided by Hunan Shaoyang Tiantang Additive Chemical Co., Ltd.; the cement is ordinary Portland cement with PO 42.5; the silica fume is high-quality silica fume provided by Beijing Zhongdetai Technology Co., Ltd., with SiO2 content greater than 93%, average particle size of 0.1-0.3 μm, and specific surface area of ​​18×104-20×104 cm 2 / g; bulk density is 175 kg / m 3 The fly ash used was first-grade fly ash produced by a manufacturer in Gongyi, Henan. The water reducer was purchased from the high-performance polycarboxylic acid liquid water reducer HD-PCA201 produced by Hunan Jinhuada Company. The steel fiber used was copper-plated steel fiber provided by Kairuida Co., Ltd. The length of the steel fiber was 12 ~14 mm and the diameter was 0.18~0.23 mm. The aggregate was local river sand in Xi'an, Shaanxi Province. The river sand was sieved with a 2.36 mm square hole to remove particles with larger particle size. In order to achieve the required mud content, the remaining river sand was washed with water and then placed in an oven set at 110 ℃ for 3 h to remove the moisture contained.

[0022] The CLDH preparation method used in the specific implementation of the present invention is as follows: The LDHs were placed in a muffle furnace, the calcination temperature was set to 550°C, and the high-temperature calcination was performed for 5 h. After the high-temperature calcination, the temperature in the muffle furnace was naturally cooled to room temperature, and the product was taken out and passed through a 100-mesh standard sieve to obtain CLDH.

[0023] The HPC basic formula used in the specific implementation of the present invention is shown in Table 1.

[0024] Table 1 Basic mix ratio of HPC (kg / m 3 )

[0025] The present invention provides a method for preparing an EVA / LDHs modifier, comprising the following steps: (1) calcining LDHs at 500-600 °C for 4-6 h at a heating rate of 7-9 °C / min, cooling to room temperature, and sieving with a sieve size of 100 mesh to obtain CLDH; (2) Add EVA and the CLDH obtained in (1) to deionized water in a mass ratio of 1:(0.5-1.5):50, heat to 90-95 °C for 0.5-1 h, stir at a speed of 650-700 r / min, and then let stand until cooled to room temperature to obtain an EVA / LDHs solution; (3) The EVA / LDHs solution obtained in (2) was centrifuged at (4000±50) r / min for 30-40 min, dried at 95-105°C for 3-5 h, and then ground and sieved with a 60-mesh sieve to obtain an EVA / LDHs modifier.

[0026] The present invention also provides an EVA / LDHs modifier, which is obtained based on the preparation method of the above-mentioned EVA / LDHs modifier.

[0027] The present invention also provides an application of an EVA / LDHs modifier as an admixture for preparing high-performance concrete, wherein the EVA / LDHs modifier accounts for 2% to 8% of the mass of the concrete and is used for preparing cement concrete structures with high durability requirements in seasonally frozen areas.

[0028] The preparation and curing method of the concrete specimen in the specific implementation manner of the present invention is as follows: (1) Add cement, silica fume and fly ash into the mixing pot of a planetary mixer and stir at a low speed for 30 seconds to make the powder materials evenly mixed and reduce agglomeration; (2) Mix water and water-reducing agent solution evenly and slowly add them to the mixing pot. Stir at low speed for 60 seconds. Then, use a trowel to gently tap the sides of the mixing pot to allow a small amount of powder material attached to the pot wall to fall to the bottom of the mixing pot and stir at high speed for 30 seconds to form a cohesive cementitious material. (3) Stir at low speed for 60 seconds. Add sand evenly within the first 30 seconds. At this time, the fluidity of cement mortar in the mixing pot gradually decreases. Stir at high speed for another 30 seconds until the concrete in the mixing pot regains fluidity. (4) Stir at low speed for 30 seconds and slowly spread the steel fibers into the mixing pot to avoid uneven distribution of the steel fibers, and then stir at high speed for 30 seconds; (5) Stop stirring and use a spatula to scrape the mixer blades and the cement mortar attached to the surrounding areas into the mixing pot. Finally, stir at a low speed for 30 seconds. (6) After the mixing is completed, the cement mortar is poured into a test mold with the sides and bottom coated with a release agent, thus completing the preparation of the cement mortar specimen; (7) After pouring the mixed cement mortar, cover the surface of the specimen with a wet cloth and leave it at room temperature (20±5)℃ and relative humidity greater than 50% for 12 h. Then demould and place the specimen in a standard curing box set at (20±2)℃ and relative humidity greater than 95% for curing to ensure that a layer of water film remains on the surface of the specimen and cure to the corresponding age.

[0029] Embodiment 1: like Figure 1 As shown, the present invention provides a method for preparing an EVA / LDHs modifier, comprising the following steps: (1) LDHs were calcined at 500 °C for 4 h at a heating rate of 7 °C / min, cooled to room temperature, and sieved with a 100-mesh sieve to obtain CLDH; (2) EVA and the CLDH obtained in (1) were added to deionized water in a mass ratio of 1:0.5:50, the temperature was raised to 90 °C for 0.5 h, and the mixture was stirred at a speed of 650 r / min, and then allowed to stand and cooled to room temperature to obtain an EVA / LDHs solution; (3) The EVA / LDHs solution obtained in (2) was centrifuged at 3950 r / min for 30 min, dried at 95 °C for 3 h, ground, and sieved with a 60-mesh sieve size to obtain an EVA / LDHs modifier.

[0030] The present invention also provides an EVA / LDHs modifier, which is obtained based on the preparation method of the above-mentioned EVA / LDHs modifier.

[0031] The present invention also provides an application of an EVA / LDHs modifier as an external admixture for preparing high-performance concrete, wherein the EVA / LDHs modifier accounts for 2% of the mass of the concrete and is used for preparing cement concrete structures with high durability requirements in seasonally frozen areas.

[0032] Embodiment 2: like Figure 1 As shown, the present invention provides a method for preparing an EVA / LDHs modifier, comprising the following steps: (1) LDHs were calcined at 550 °C for 5 h at a heating rate of 8 °C / min, cooled to room temperature, and sieved with a 100-mesh sieve to obtain CLDH; (2) 10 g of EVA and 10 g of CLDH obtained in (1) were added to 500 mL of deionized water, the temperature was raised to 90 °C for 0.5 h, and the mixture was stirred at 700 r / min. The mixture was then allowed to stand for 1 h and cooled to room temperature to obtain an EVA / LDHs solution. (3) The EVA / LDHs solution obtained in (2) was centrifuged at 4000 r / min for 40 min, dried at 105 °C for 4 h, and then ground and sieved with a 60-mesh sieve to obtain an EVA / LDHs modifier.

[0033] The present invention also provides an EVA / LDHs modifier, which is obtained based on the preparation method of the above-mentioned EVA / LDHs modifier.

[0034] The present invention also provides an application of an EVA / LDHs modifier as an admixture for preparing high-performance concrete, wherein the EVA / LDHs modifier accounts for 4% of the mass of the concrete and is used for preparing cement concrete structures with high durability requirements in seasonally frozen areas.

[0035] Embodiment 3: like Figure 1 As shown, the present invention provides a method for preparing an EVA / LDHs modifier, comprising the following steps: (1) LDHs were calcined at 600 °C for 6 h at a heating rate of 9 °C / min, cooled to room temperature, and sieved with a 100-mesh sieve to obtain CLDH; (2) EVA and the CLDH obtained in (1) were added to deionized water in a mass ratio of 1:1.5:50, the temperature was raised to 95 °C for 1 h, and the mixture was stirred at a speed of 700 r / min, and then allowed to stand and cooled to room temperature to obtain an EVA / LDHs solution; (3) The EVA / LDHs solution obtained in (2) was centrifuged at 4050 r / min for 40 min, dried at 105 °C for 5 h, ground, and sieved with a 60-mesh sieve size to obtain an EVA / LDHs modifier.

[0036] The present invention also provides an EVA / LDHs modifier, which is obtained based on the preparation method of the above-mentioned EVA / LDHs modifier.

[0037] The present invention also provides an application of an EVA / LDHs modifier as an external admixture for preparing high-performance concrete, wherein the EVA / LDHs modifier accounts for 8% of the mass of the concrete and is used for preparing cement concrete structures with high durability requirements in seasonally frozen areas.

[0038] Example 4: Effect of reaction conditions on modifiers Evaluation method of composite material synthesis effect: At room temperature of 25°C, the density of deionized water is about 1 g / mL, while the density of EVA latex powder is usually 0.929~0.974 g / cm 3 The density of EVA latex powder is smaller than that of deionized water, and the molecular chain of EVA latex powder is water-soluble due to the hydrophilic groups contained in it. After EVA latex powder is dissolved in water, it will appear as an emulsion suspension; the density of deionized water will gradually decrease with the increase of temperature. The EVA emulsion is gradually heated to 90℃ with a magnetic stirrer and stirred at 500 r / min for 30 min to fully stir the EVA emulsion. After the stirring is completed, the solution is allowed to stand and it is found that the EVA emulsion is still in the form of an emulsion suspension. Therefore, it shows that as the temperature of the EVA emulsion solution increases, the density of the EVA emulsion particles is still lower than that of deionized water, and they will be suspended in the deionized water, and the solution is still in the form of an emulsion suspension.

[0039] The density of CLDH and LDHs is about 2 g / cm 3 , which is much larger than the density of EVA emulsion. After CLDH is mixed with EVA emulsion, CLDH will restore its original layered hydroxide structure to form LDHs due to its good adsorption and structural memory effect, and adsorb EVA polymer to form EVA / LDHs. Its density will still be greater than that of deionized water, and all of them will accumulate at the bottom of the flask, such as Figure 2 As shown; therefore, the synthesis effect of EVA / LDHs can be indirectly reflected according to the concentration of the upper EVA suspension (absorbance of the suspension) of the EVA / LDHs solution prepared after the reaction.

[0040] (1) Effect of reaction temperature on modifier 10 g EVA and 15 g CLDH were added to 500 mL deionized water and heated to 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, and 90°C, and stirred at 700 r / min for 1 h. After the reaction was completed, the mixture was allowed to stand and cooled to room temperature to obtain EVA / LDHs solution. The absorbance of the upper suspension of the EVA / LDHs solution at different reaction temperatures was as follows: Figure 3 shown.

[0041] (2) Effect of reaction time on modifier 10 g EVA and 15 g CLDH were added to 500 mL deionized water, heated to 90 °C, and stirred at 700 r / min for a period of time (0.25 h, 0.5 h, 1 h, 1.5 h, 2 h, 3 h, 4 h). After the reaction was completed, the mixture was allowed to stand and cooled to room temperature to obtain an EVA / LDHs solution. The absorbance of the upper suspension of the EVA / LDHs solution at different reaction times was as follows: Figure 4 shown.

[0042] (3) Effect of raw material ratio on modifier 10 g EVA and a certain amount of CLDH (5 g, 10 g, 15 g, 20 g, 25 g, 30 g) were added to 500 mL deionized water, heated to 90 °C, and stirred at 700 r / min for 0.5 h. After the reaction was completed, the mixture was allowed to stand and cooled to room temperature to obtain EVA / LDHs solution. The absorbance of the upper suspension of EVA / LDHs solution with different raw material ratios was as follows: Figure 5 shown.

[0043] Taking into account the optimal reaction parameters in the composite preparation process of EVA and CLDH, the reaction temperature was selected to be 90 °C, the reaction time was controlled to be 0.5 h, the reaction ratio was 500 mL of deionized water, and the raw materials were 10 g of EVA and 10 g of CLDH.

[0044] However, in actual application, the effect of the EVA / LDHs modifier obtained when the reaction temperature is 90~95 ℃, the reaction time is 0.5~1 h, and the mass ratio of EVA and CLDH is 1:(0.5~1.5) is still acceptable. Therefore, in the specific production application process, the preparation process of EVA / LDH can be adjusted according to actual conditions to pursue the highest economic value.

[0045] like Figure 6 As shown, it is the SEM picture of the CLDH of the present invention. After high-temperature calcination, the well-arranged layered structure of LDHs is destroyed, and the generated CLDH has a relatively obvious peeled-off lamellar structure. The lamellar layer is flat and shriveled, and larger pores are generated, and the specific surface area of ​​the structure is increased.

[0046] like Figure 7 , which is a SEM picture of the EVA latex powder of the present invention, the EVA latex powder is mainly composed of a structure of approximately spherical particles, and the surface of the particles is relatively flat.

[0047] like Figure 8 As shown, it is the SEM picture of the EVA / LDHs composite material of the present invention. The EVA / LDHs composite material is composed of a particle structure similar to an ellipsoid shape, and the particle surface contains irregular exfoliated lamellae. CLDH combines with the EVA spherical particles through adsorption, the contact area between the constituent particles becomes larger, and the overall adsorption is improved.

[0048] like Fig. 9As shown, the XRD patterns of different hydrotalcites at 10°~70° of the present invention are shown. The LDHs have good crystallinity and a complete layered structure. After the LDHs are pretreated by high-temperature calcination at 550°C, the layered hydroxide structure is destroyed to generate a composite calcium aluminum oxide CLDH. In the EVA / LDHs composite material, the hydrotalcite interacts with the EVA latex powder to present an exfoliated layered structure.

[0049] like Fig.10 As shown, it is the XRD spectrum of different hydrotalcites of 2°~10° of the present invention. In the EVA / LDHs composite material, EVA is not inserted into the interlayer of LDHs in the form of a polymer chain, but through the strong physical adsorption of CLDH, the layered structure is peeled and attached to the surface of the EVA polymer group.

[0050] like Fig.11 As shown, it is the infrared spectra of EVA, CLDH and EVA / LDHs of the present invention. After LDHs is calcined to form CLDH, the interlayer water molecules are gradually removed and the layer hydroxide structure gradually collapses. CLDH shows strong adsorption. In the prepared EVA / LDHs composite material, the EVA latex particles interact with CLDH, and EVA is successfully adsorbed into the structure of LDHs.

[0051] Example 5: Chloride ion curing experiment Generally speaking, the lower the chloride ion concentration in the filtrate, the better the adsorption and solidification effect of such substances on chloride ions. Under the conditions of the adsorption of chloride ions by EVA / LDHs, LDHs, and CLDH, the residual chloride ion content in the test solution is shown in detail. Fig.12 .

[0052] Depend on Fig.12 It can be seen that after the three raw materials are used as admixtures to replace part of the cement mass, the remaining chloride ion content in the solution decreases, but the degree of reduction is different; EVA / LDHs and CLDH have a better adsorption effect on free chloride ions, and the adsorption of chloride ions becomes stronger with the higher the dosage, while LDHs without any treatment has poor adsorption performance for chloride ions.

[0053] The analysis shows that the interlayer anion CO3 2- The charge number is higher than Cl - High, interlayer CO3 2- The bonding force between the layers is strong, so Cl - It is difficult for LDHs to enter the interlayer through ion exchange. - Adsorption is only through surface physical adsorption and shows poor Cl - Adsorption effect.

[0054] Example 6: Effects of different modifiers on HPC (1) Fluidity test: Conducted in accordance with the specification "Testing Procedures for Cement and Cement Concrete for Highway Engineering" JTB 3320-2020; (2) Flexural strength test: conducted in accordance with the specification "Test Procedures for Cement and Cement Concrete for Highway Engineering" JTB3 320-2020; (3) Compressive strength test: The specimens broken by the flexural test are used, and the compressive test is carried out immediately after the flexural test. The compressive surfaces of the specimens are the two side surfaces of the formed specimens. The loading rate of the press is controlled within the range of 2400±200 N / s. When the specimen is damaged by pressure, the failure load of the specimen is recorded and the compressive strength is calculated.

[0055] Rc=Fc / A Where: Rc is the compressive strength of the specimen (MPa); Fc is the failure load of the specimen (N); A is the compressive area of ​​the specimen, A=40 mm×40 mm (mm 2 ).

[0056] Effects of single-doping EVA, single-doping CLDH, multiple-doping EVA+CLDH, and single-doping EVA / LDHs of Example 2 on the physical and mechanical properties of HPC are shown in Figure 2. Fig.13 , Fig.14 And as shown in Table 2.

[0057] Table 2 Compressive and flexural strength of HPC with different modifier dosages

[0058] Among them, A1, A2, A3, and A4 correspond to specimens with EVA dosage of 2%, 4%, 6%, and 8%, respectively; B1, B2, B3, and B4 correspond to specimens with CLDH dosage of 1%, 2%, 3%, and 4%, respectively; A2B1, A2B2, A2B3, and A2B4 correspond to specimens with EVA dosage fixed at 4% and CLDH dosage of 1%, 2%, 3%, and 4%, respectively; C1, C2, C3, and C4 correspond to specimens with EVA / LDHs dosage of 2%, 4%, 6%, and 8%, respectively.

[0059] It can be seen from the test results that with the increase of EVA / LDHs dosage, the fluidity of HPC will gradually decrease, but the effect on the working performance of HPC is smaller than that of single EVA, single CLDH and composite 4% EVA+CLDH; the composite material EVA / LDHs not only has the advantage of single EVA to improve the flexural properties of HPC, but also plays the role of CLDH in promoting the early strength formation of HPC, and has little effect on the later compressive strength of HPC; the addition of EVA / LDHs can increase the flexural-compression ratio of HPC and improve the toughness of HPC structure, and is better than the single CLDH on the toughness enhancement effect of HPC. Single 4% EVA and composite 4% EVA+1% CLDH have the best effect on the toughness enhancement of HPC, but the addition of 4% EVA will reduce the compressive strength of HPC.

[0060] Example 7: Effects of different modifiers on HPC durability (1) Chloride ion penetration resistance: The rapid determination method of chloride ion diffusion coefficient of concrete (RCM method) was used for evaluation. The specific process was carried out in accordance with the "Test Procedure for Cement and Cement Concrete for Highway Engineering" JTB3420-2020, and steel fiber was not considered for each group of raw materials to reduce interference with the test results. After the specimens were cast and cured according to the specifications, the specimens were vacuum saturated with water, and then the air pressure was reduced to 1~5k Pa within 5 minutes and maintained for 3 hours. Subsequently, the prepared saturated Ca(OH)2 solution was injected into the container and the specimens were immersed for 1 hour; after the vacuum immersion was completed, the vacuum container was restored to normal pressure and continued to be immersed for (18±2) hours, and then the specimens were blown dry for RCM test. The test results are as follows Fig.15 shown.

[0061] (2) Frost resistance: Refer to the "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete" (GB / T50082-2009) and use the slow freezing method. Prepare the specimens according to the concrete durability specifications. The specimen size is 10 cm×10 cm×10 cm cube. When the specimens reach the standard curing age of 24 days, take them out and soak them in water at a temperature of 20±2℃ for 4 days. After the soaking is completed, the freeze-thaw cycle test can be started. The temperature of the specimen was set at -20~-18℃ during freezing, and the water temperature was controlled at 18~20℃ during melting. The freezing and melting time of the specimen was 4 h. After each melting, a freeze-thaw cycle was completed. After each freeze-thaw cycle test, the appearance of the specimen was carefully observed and the mass of the specimen was weighed. If the specimen had freeze-thaw erosion and the mass loss rate before and after the cycle was ≥5%, the freeze-thaw cycle test was stopped and the number of freeze-thaw cycles was recorded. If there was no obvious erosion on the appearance of the specimen and the mass loss rate was ≤5%, and the freeze-thaw cycle of the specimen reached 160 times (that is, the antifreeze grade reached D200), the test was stopped and the mass of the specimen at this time was recorded. The results are as follows: Fig.16 , Fig.17 , Fig.18 , Fig.19 shown.

[0062] The change trend of the strength and strength loss rate of the specimens added with EVA / LDHs alone shows that the compressive strength of the specimens added with EVA / LDHs after freeze-thaw cycles is increased to a certain extent, and the strength loss rate of HPC after freeze-thaw cycles is reduced, thereby improving the frost resistance of HPC; when 4% EVA / LDHs is added, the compressive strength of the specimens after freeze-thaw cycles is still 90.4 MPa, and the strength loss rate is reduced to 8.1%, which is 31.3% less than that of the blank group, and the reduction in strength loss rate is the largest compared with single EVA, single CLDH and multiple EVA+CLDH; therefore, it is shown that EVA / LDHs has the best effect on improving the frost resistance of HPC specimens.

[0063] EVA / LDHs composite materials can make full use of the nucleation effect of calcium ions in LDHs to promote the growth of hydration products. As the number of hydration products around EVA increases, EVA will be in close contact with the hydration products to form a denser concrete structure, reducing the amount of moisture that penetrates into the structure from the outside in terms of density. Secondly, the LDHs interlayers also have a water storage function. The moisture that penetrates into the structure can be absorbed by LDHs, and the layered structure can also block further penetration of moisture. Therefore, EVA / LDHs composite materials have more advantages than single-doped EVA, single-doped CLDH and multi-doped EVA+CLDH.

[0064] Salt-freeze resistance: refer to the "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete" (GB / T50082-2009), adopt the slow freezing method, the specimen size is 100 mm×100 mm×100 mm cube, the curing age is 28 days, of which 24 days are cured under standard curing conditions, and the last 4 days are immersed in water curing (water temperature is 20±2℃). After the curing, wipe the surface moisture with a wet cloth and record the initial average mass of the specimen; use a controllable horizontal freezer to control the temperature at -20~-18℃, the specimen freezing time is 4 h, and after freezing, move the specimen to a salt solution with a water temperature of 18~20℃ (mass ratio is 97% H2O, 3% NaCl), and melt the specimen for 4 hours. h, and a freeze-thaw cycle is completed after the melting is completed; during the test, after every 25 freeze-thaw cycles, carefully observe the appearance of the specimen and weigh the mass of the specimen. If the specimen has freeze-thaw erosion and the mass loss rate is ≥5%, the salt-freeze cycle test is stopped and the number of freeze-thaw cycles is recorded; if the specimen has no obvious erosion on the appearance and the mass loss rate is ≤5%, when the freeze-thaw cycle of the specimen reaches 160 times, that is, the antifreeze grade is above D200, stop the test and record the mass of the specimen at this time. The results are as follows Fig. 20 , Fig.21 , Fig. 22 , Fig.23 , Fig.24 shown.

[0065] In summary, the addition of EVA / LDHs can improve the chloride ion permeability resistance of HPC. When the addition amount of EVA / LDHs is 6%, the improvement effect of HPC's chloride ion permeability resistance is the best, which is similar to the improvement effect of single addition of 3% CLDH and compound addition of 4% EVA+2% CLDH on HPC's chloride ion permeability resistance, and is better than the improvement effect of single addition of EVA on HPC's chloride ion permeability resistance; with the gradual increase of the addition amount of EVA / LDHs, the improvement effect on the antifreeze performance of HPC first increases and then decreases. When 4% EVA / LDHs is added, the improvement effect on the antifreeze performance of HPC is the best, and is better than the improvement of the antifreeze performance of HPC by single addition of EVA, single addition of CLDH and compound addition of 4% EVA+CLDH degree; after the specimens experienced anti-salt-freeze cycles, the surfaces of the HPC specimens added with EVA, CLDH, and EVA / LDHs all had varying degrees of exfoliation and erosion. When the EVA / LDHs content was 6%, the anti-salt-freeze performance of HPC was improved best, followed by the compound addition of 4% EVA+CLDH, while the improvement effect of single EVA latex powder on HPC was not significant; compared with the HPC specimens added with single EVA and single CLDH, the spatial distribution of hydration products formed by the HPC specimens added with EVA / LDHs was denser, and the volume of multiple harmful pores and harmful pores in the structure was greatly reduced. Therefore, on a macroscopic level, it had a better improvement effect on the durability of HPC, such as resistance to chloride ion permeability, antifreeze, and anti-salt-freeze performance.

[0066] Example 8: An EVA / LDHs modified HPC repair material, comprising: Cement 760 kg / m 3 、Silica fume 130 kg / m 3 、Fly ash 110 kg / m 3 、EVA / LDHs 40 kg / m 3 、River sand 1220kg / m 3 , water 190 kg / m 3 , water reducing agent 30 kg / m 3 , Steel fiber 25 kg / m 3 .

[0067] According to the material characteristics of EVA / LDHs modified HPC and the actual construction environment on site, the rapid repair construction of bridge expansion joint concrete is as follows: Fig.25 The specific repair effect is as shown in Fig.26 shown.

[0068] (1) Raw material preparation: The traffic volume of Changchun Ring Expressway is large. In order to shorten the construction time of on-site workers and ensure the on-site safety of construction personnel, before the on-site expansion joint repair construction, the volume of expansion joint casting is calculated, and the required cement, silica fume, fly ash, EVA / LDHs powder materials and a certain proportion of river sand are mixed in advance using a hand-push drum mixer for 60 seconds, and then packed into waterproof woven bags for on-site construction; (2) Construction equipment preparation: Equipment for chiseling and cleaning old concrete: generator, electric hammer (hammer frequency 3200 times / min), high-pressure air gun, diesel concrete cutter, shovel; Equipment for pouring new concrete: electronic scale (50 kg), hand-push drum mixer, hand-held vibrator, trowel; (3) Control of the construction area: Before the construction team enters the site for maintenance and repair, reflective traffic cones should be placed within 100 m before and after the construction area to ensure that passing vehicles have enough reaction time to avoid the traffic. (4) Removal and cleaning of old concrete: First, use a diesel concrete cutter to cut along the interface between the asphalt surface layer and the old concrete to avoid damaging the steel bars in the anchoring area. The cutting depth is controlled at 3-5 cm to ensure that the cut surface is flat and straight. Then, use an electric hammer to chisel out the old concrete in the cut surface to the bottom of the old concrete surface layer. At the same time, the loose concrete at the bottom and around should also be chiseled out. It is forbidden to damage the main structure of the bridge during the construction process. During the chiseling process, larger concrete blocks can be removed with a shovel. After the chiseling is completed, use the impact force of a high-pressure water gun and a high-pressure air gun to clean the broken concrete and dust scattered around and at the bottom of the anchoring area to increase the roughness of the old concrete surface and the surrounding of the anchoring area, strengthen the interface bonding between the newly poured surface layer and the bottom concrete, and chisel out and clean the old concrete. (5) Check the connection of steel bars and the mixing process of concrete: After cleaning the old concrete, check the embedded steel bars and straighten, weld and tie the bent steel bars. If the steel bars are partially rusted and corroded, they should be manually rusted. EVA / LDHs modified HPC consists of a large number of raw materials. In order to shorten the on-site construction time, two hand-push drum mixers are used for simultaneous mixing and construction. First, sprinkle a small amount of water into the mixer to moisten the surrounding area of ​​the mixer, and then pour the mixed cementitious material and river sand that have been pre-packed in a woven bag into the mixer for mixing. Then pour a certain proportion of water and water reducer prepared in advance into the mixer and stir for 120 seconds. If the outdoor weather is dry and hot, the water loss is too fast and the fluidity is poor, a small amount of water can be added or the stirring time can be extended. Finally, the weighed steel fiber is evenly spread on the surface of the cement paste with tweezers or other tools, and continue to stir for 60 seconds. s; After mixing, pouring starts from the high part of the expansion joint transverse slope. The newly mixed concrete will flow to the low part of the transverse slope and fill the gaps around and at the bottom of the transition zone of the expansion joint due to its good self-compacting ability; At the same time, attention should be paid to shortening the pouring interval time of the two hand-push drum mixers to prevent the pouring time of the new and old concrete from being too long and affecting the pouring quality; (6) Vibration and finishing of fresh concrete: After the expansion joint anchoring area is poured, vibrate horizontally with a vibrator to remove a small amount of bubbles inside the concrete and increase the compactness of the concrete structure. Since HPC has good working performance and self-compacting properties, vibrate horizontally several times along the vertical direction of the roadway until bubbles are observed to no longer float up. During the vibration process with the vibrator, the surface condition of the fresh concrete should be carefully observed to avoid the floating slurry due to excessive vibration. After the concrete is vibrated, it should be quickly finished when the concrete loses its plasticity and no longer flows (15-20 minutes) to prevent adverse effects of weather, wind and other factors on the concrete surface. No finishing treatment is performed after finishing. If there is slight floating slurry after hardening, it is advisable to use a polishing treatment. Finally, the concrete flowing out of the expansion joint and the roadway should be handled in a timely manner to avoid coagulation and hardening in a short period of time. (7) Maintenance and opening to traffic: After the newly mixed concrete surface is finished, it should be covered with plastic film for curing in time, and a small amount of water should be sprinkled on the film and sprinkled again after an interval of 12 hours to reduce the impact of the external environment on cement hydration, ensure the early strength formation of concrete and avoid cracks on the concrete surface due to rapid evaporation of water. Since the compressive strength of the newly mixed EVA / LDHs modified HPC and the interlayer bonding of the new and old concrete interfaces can meet the requirements of opening to traffic after 24 hours, traffic can be opened to vehicles 24 hours after the concrete pouring and vibration is completed.

[0069] After testing, 4% EVA / LDHs HPC meets the conditions for opening traffic one day after the construction and pouring of the bridge expansion joint; based on the actual project, a construction technology scheme for the rapid repair of bridge expansion joints in seasonally frozen areas with HPC mixed with EVA / LDHs is proposed, which provides a reference for practical engineering applications. For the expansion joint of the two-way four-lane road, the raw material cost of HPC mixed with EVA / LDHs as a repair material is 210.4 yuan less than that of traditional repair materials, which has good direct economic benefits. The application of EVA / LDHs modified HPC not only reduces the number of operation maintenance and repairs, and ensures the driving safety of passing vehicles, but also contains raw materials such as fly ash and silica fume that are unfavorable to the ecological environment, and has significant social and economic effects.

[0070] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing an EVA / LDHs modifier, characterized in that: The following steps are involved: S1, calcining the lamellar hydrotalcite, cooling it to room temperature, and sieving it to obtain a lamellar calcined hydrotalcite; S2, adding ethylene-vinyl acetate latex powder and the lamellar calcined hydrotalcite obtained in S1 into deionized water, heating and stirring, and then standing and cooling to room temperature to obtain an EVA / LDHs solution; S3, the EVA / LDHs solution obtained in S2 is centrifuged, dried, ground and sieved in sequence to obtain an EVA / LDHs modifier.

2. The method for preparing an EVA / LDHs modifier according to claim 1, characterized in that: The calcination temperature in S1 is 500-600°C, the calcination time is 4-6 h, and the calcination heating rate is 7-9°C / min.

3. The method for preparing an EVA / LDHs modifier according to claim 1, characterized in that: The mesh size of the sieve in S1 is 100 mesh.

4. The method for preparing an EVA / LDHs modifier according to claim 1, characterized in that: The mass ratio of ethylene-vinyl acetate latex powder, lamellar calcined hydrotalcite and deionized water in S2 is 1:(0.5-1.5):

50.

5. The preparation method of an EVA / LDHs modifier according to claim 1, characterized in that: The heating temperature in S2 is 90-95°C, the heating time is 0.5-1 h; and the stirring speed is 650-700 r / min.

6. The preparation method of an EVA / LDHs modifier according to claim 1, characterized in that: The centrifugal speed in S3 is (4000±50) r / min, and the centrifugal time is 30~40 min.

7. The preparation method of an EVA / LDHs modifier according to claim 1, characterized in that: The drying temperature in S3 is 95-105° C., and the drying time is 3-5 h.

8. The method for preparing an EVA / LDHs modifier according to claim 1, characterized in that: The mesh size of the sieve in S3 is 60 meshes.

9. An EVA / LDHs modifier, characterized in that: The method for preparing the EVA / LDHs modifier is based on any one of claims 1 to 8.

10. Use of an EVA / LDHs modifier as an admixture for preparing high performance concrete according to claim 9, characterized in that: EVA / LDHs modifier accounts for 2% to 8% of the mass of concrete and is used to prepare cement concrete structures with high durability requirements in seasonally frozen areas.